Malicious unauthorised access to computer programs and data in Malaysia. - Rahman, Rizal (Commonwealth Law Bulletin, 2021)
Access to programs and data is the key to cybercrimes. It is mainly done through various means, but the Malaysian law is broad enough to cover any means adopted by the criminals. This article discusses relevant provisions from the Malaysian Computer Crimes Act governing this illegal activity, and cites relevant cases on the matter. To ensure that readers understand the real scenario, the author has conducted library research and fieldworks for sufficient deliberation on the matter, since cases in the lower courts were unreported. The need for enhancing the mechanisms is highlighted to be pondered by the relevant enforcement authority.